Authenticated Key Agreement with Rekeying for Secured Body Sensor Networks - Kyngn Jung Kim; Ahmed Saleh Tolba; Mohamed Hamdy Eldefrawy; Muhammad Khurram Khan; Khaled Alghathbar (Sensors, 2011)
Many medical systems are currently equipped with a large number of tiny, non-invasive sensors, located on, or close to, the patient’s body for health monitoring purposes. These groupings of sensors constitute a body sensor network (BSN). Key management is a fundamental service for medical BSN security. It provides and manages the cryptographic keys to enable essential security features such as confidentiality, integrity and authentication. Achieving key agreement in BSNs is a difficult task. Many key agreement schemes lack sensor addition, revocation, and rekeying properties, which are very important. Our proposed protocol circumvents these shortcomings by providing node rekeying properties, as well as node addition and revocation. It proposes a key distribution protocol based on public key cryptography—the RSA (Rivest, Shamir and Adleman) algorithm, and the DHECC (Diffie-Hellman Elliptic Curve Cryptography) algorithm. The proposed protocol does not trust individual sensors, and partially trusts the base station (hospital). Instead of loading full pair-wise keys into each node, after installation our protocol establishes pair-wise keys between nodes according to a specific routing algorithm. In this case, each node doesn’t have to share a key with all of its neighbors, only those involved in the routing path; this plays a key role in increasing the resiliency against node capture attacks and the network storage efficiency. Finally we evaluate our algorithm from the BSN security viewpoint and evaluate its performance in comparison with other proposals.